Pamiętnik z ćwiczeń filozoficznych = Diary of Philosophical Exercises - Femiak, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article quotes extensively from the philosophical diary of a student practicing spiritual exercises used in philosophical counseling classes. The purpose of these exercises is to solidify the so-called soft skills, attentiveness, making oneself present, knowing oneself, active thinking and practical use of one`s cognitive intuition. The described exercise scenarios are intended to shape the attitude of future philosophical coaches, counselors and therapists. They can also be successfully used during sessions with clients.
Keywords: pamiętnik filozoficzny; ćwiczenia duchowe; scenariusz ćwiczeń; uobecnienie siebie; obserwacja; "zrób wiem, że nic nie wiem"; "obojętność na rzeczy obojętne"; trzy części duszy; milczenie; "oddawanie racji"; philosophical diary; spiritual exercises; exercise scenario; making oneself present; observation; "do I know that I know nothing"; "indifference to indifferent things"; three parts of the soul; silence; "rendering right"